IDENTIFICATION OF GLUCAGON-LIKE PEPTIDE-1 RECEPTOR LIGANDS AND THEIR IMPACTS IN THE TREATMENT OF TYPE 2 DIABETES (Arquivos do Mudi, 2023)
Diabetes mellitus is a chronic disease responsible for one of the world's most common publichealth problems. Its prevalence, comorbidities, and medical costs assume a dramatic scale andan efficient response to these projections is the intensified search for new agents andapproaches. Therefore, for the development of potential glucagon-like peptide-1 receptor(GLP-1R) agonists, a virtual screening technique based on molecular docking using thecrystallographic structure of human GLP-1R as a target was employed in two productlibraries natural, Zinc15 and Sigma-Aldrich. The structure of the protein (PDB id 6X1A)bound to Pfizer compound PF-06882961 was modeled by homology. The best-presentedmodel was inserted into a lipid bilayer and subjected to structure minimization, redocking,virtual screening, and molecular dynamics simulations. After simulations, 39 molecules wereselected and analyzed by predicting bioactivity and pharmacokinetics resulting in 4 ligands(Zinc1901002, Zinc1901002m, 336188752 e 336185530). The ligands were inserted into the6X1A crystallographic structure to analyze the conformational changes and the stability ofprotein-ligand interactions through molecular dynamics simulations for 50 ns. We observedthat the ligands coupled to GLP-1R remained stable without conformational changesthroughout the simulation, indicating that the selected ligands can act as potential GLP-1Ragonists.